2002
DOI: 10.1046/j.1432-1033.2002.03156.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a chemosensory protein (ASP3c) from honeybee (Apis mellifera L.) as a brood pheromone carrier

Abstract: Chemosensory proteins (CSPs) are ubiquitous soluble small proteins isolated from sensory organs of a wide range of insect species, which are believed to be involved in chemical communication. We report the cloning of a honeybee CSP gene called ASP3c, as well as the structural and functional characterization of the encoded protein. The protein was heterologously secreted by the yeast Pichia pastoris using the native signal peptide. ASP3c disulfide bonds were assigned after trypsinolysis followed by chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(115 citation statements)
references
References 62 publications
5
110
0
Order By: Relevance
“…Obp13, 14, 15, and chemosensory protein 3 (ASP3) were identified in the hemolymph of A. mellifera summer workers (Bogaerts et al 2009), and Obp14 was found in winter worker hemolymph (Erban et al 2013). Briand et al (2002) observed that CSP3 is a brood pheromone carrier in A. mellifera . Foret et al (2007) found CSP3 in late larvae, but no detectable expression of CSP3 was found during the initial stages of pupal development (24 h); however, the CSP3 transcripts were, again, detectable in red-eye pupae, and the level gradually increased as the head became dark.…”
Section: Olfaction-odorant-binding and Chemosensory Proteinsmentioning
confidence: 93%
“…Obp13, 14, 15, and chemosensory protein 3 (ASP3) were identified in the hemolymph of A. mellifera summer workers (Bogaerts et al 2009), and Obp14 was found in winter worker hemolymph (Erban et al 2013). Briand et al (2002) observed that CSP3 is a brood pheromone carrier in A. mellifera . Foret et al (2007) found CSP3 in late larvae, but no detectable expression of CSP3 was found during the initial stages of pupal development (24 h); however, the CSP3 transcripts were, again, detectable in red-eye pupae, and the level gradually increased as the head became dark.…”
Section: Olfaction-odorant-binding and Chemosensory Proteinsmentioning
confidence: 93%
“…Although a few studies have sought to implicate various small soluble proteins in pheromone recognition (17,(20)(21)(22)(23), it seems more likely that these proteins are involved in generic odorant solubilization and play little role in odor coding (24,25). The only known hymenopteran pheromone ligand-receptor pair to date is the honey bee (Apis mellifera) queen pheromone 9-ODA and the OR AmelOR11 (26).…”
Section: Significancementioning
confidence: 99%
“…Furthermore, several haemolymph proteins were resolved by twodimensional gel electrophoresis that were not correlated with microbial challenge, among them apolipophorin-III (ApoLp-III), another component of the lipid transport system (Weers and Ryan, 2006), antennal-specific protein 3c (ASP3c), a soluble chemosensory protein (Briand et al, 2002;Forêt et al, 2007), and three members of the odorant binding-like protein (OBP) family, OBP 13, OBP 14 and OBP 18. Of the three OBPs identified in the haemolymph of adult drones, OBP 14 was present also in drone larvae (Fig.2) whereas OBP 13 and OBP18 were not detected in larval haemolymph (data not shown).…”
Section: Adult Young Drones Respond To Septic Injury With a Broad Arrmentioning
confidence: 99%